Evolución del sistema ciencia, tecnología e industria en el mundo y en la UE - Sáenz Lorenzo, José Félix (2000)
The object of the present work is to analyze the Science, Tecnology and Industry (STI) policy evolution along the 20th century, in particular that of the European Union (UE), from its foundation to the present day, centering us especially in the evolution of the strategic options adopted from two different focuses: that of the scientific policy and that of the industrial policy, whose encounter point is technology. The work consists of two parts, the first one analyzing the evolution of the system of Science and Technology in Europe and in the world, paying special attention to institucional aspects and the role of the public sector in the financing and impulse to these policies, and highlighting the contrast between the development in Europe and in the USA. The second part analyzes the technological and industrial policy evolution in the UE from the Treatise of Rome (1957) to the Treatise of the Union of 1992. The analysis of this evolution will show the deep change that has taken place in the European philosophy that has passed of a technologi-cal and industrial policy exclusively based in the defense of the competition, and in the absence of intervention of the countries members, to the development, starting from the 80¹s, of an industrial policy based on the creation from a favorable environment to the Investigation and Technological Development (IDT) and in the public support to the innovation in the company